PROFESSIONAL SKEPTICISM AND INTRINSIC MOTIVATION AS DRIVERS OF AUDITORS RESPONSIBILITY FOR FRAUD DETECTION - Anak Agung Bagus Amlayasa; Ni Made Rustini; Imang Dapit Pamungkas; Sultan Syah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This study investigates the mediating roles of intrinsic motivation and professional skepticism in the relationship between self-efficacy and auditors’ responsibility in detecting fraud. Data were collected via an online survey, involving 102 auditors in Denpasar public accounting firms. The results showed that self-efficacy directly affected the intrinsic motivation variables and professional skepticism, but did not directly affect the responsibility of cheating detection. These findings support self-determination theory and social cognitive theory. Notably, intrinsic motivation and professional skepticism mediate the effect of self-efficacy on auditors' responsibility in detecting fraud. Academically, this study enriches auditing literature by showing how internal psychological traits impact ethical responsibilities. As self-efficacy alone does not directly affect detection responsibility, its influence is channeled through motivational and cognitive constructs. It addresses discussions on why self-efficacy fails to predict detection responsibility directly. From a practical standpoint, professional bodies and public accounting firms are encouraged to strengthen auditors’ self-efficacy, skepticism, and intrinsic motivation through targeted programs such as training, socialization, continuing education, and anti-fraud certification. In conclusion, the study confirms the multi-mediated model, where both intrinsic motivation and professional skepticism are are key in transforming self-efficacy into a strong sense of responsibility for fraud detection.